Teachers' Efforts to Instill Disciplinary Values through Learning Islamic Religious Education in Grade 4 Students at MIN 2 Bengkulu City - Rossaliani, Adini; Satia, Lara; Nurhikma, Nurhikma; Nasution, Adam; Manjato, Ajat (International Journal on Advanced Science, Education, and Religion, 2025)
This research is motivated by the persistent problems in instilling discipline values ​​in students in elementary schools, particularly in Islamic Religious Education (PAI) learning, which has not been fully integrated optimally into classroom learning practices. Therefore, this study aims to analyze and describe teachers' efforts in instilling discipline values ​​through PAI learning and to identify supporting and inhibiting factors that influence the process. This study uses a qualitative approach with a case study design conducted at MIN 2 Bengkulu City. Data collection techniques were carried out through non-participatory observation, semi-structured interviews, documentation, and literature studies. Data analysis used an interactive model that includes data reduction, data presentation, and conclusion drawing, with data validity testing through triangulation.The results of the study indicate that teachers' efforts to instill discipline through habituation, role modeling, rule enforcement, and the integration of Islamic values ​​in Islamic Religious Education (PAI) learning. This strategy has been proven to improve students' understanding and disciplinary behavior, such as punctuality, compliance with rules, and responsibility in completing assignments. This success is supported by a conducive school environment and clear rules, but there are still obstacles such as a lack of support from the family environment and limited learning time. Thus, it can be concluded that the strategy of habituation, role modeling, and integration of Islamic values ​​is an effective approach to instilling student discipline, although it requires support from various parties for more optimal and sustainable results.